ANALYSIS OF THE EFFECT OF THERMALLY PROCESSED OAK ON VINOMATERIALS MADE FROM LOCAL GRAPE VARIETIES OF SMALL COMBS - Ismatova Sh.N; Yuldasheva Sh.J; Sultonova O.I (Western European Studies, 2024)
The article investigated the coining of oak combs in the process of maturation of red wines from various grape varieties grown in the Bukhara region, such as Saperavi, Kaberne, Hindogni, Tavkveri. Various thermally processed tshep of oak wine has been analyzed for its effect on physicochemical indicators, taste, smell, color.
Keywords: oak combs; red wines; local grape varieties